Measuring family satisfaction with inpatient rehabilitation care. Issue 1 (8th February 2016) - Angelino, Elisabetta; Gragnano, Andrea; Miglioretti, Massimo
Abstract : Purpose: – The purpose of this paper is to investigate the psychometric characteristics of the Questionnaire of Family members' Satisfaction about the Rehabilitation (QFSR), a new questionnaire assessing the satisfaction of patients' families with the in-hospital rehabilitation service, i.e., the organizational procedure, medical treatment, relationship with nurses/other health workers, and outcome. Design/methodology/approach: – The QFSR (13 items) was administered to 1, 226 ( F =60.4 percent; mean age=57.4, SD 15 years) family members of patients admitted to two units for inpatient rehabilitation, i.e., cardiovascular and neuromotor. Findings: – Confirmatory factor analysis (CFA) confirmed the theoretical four-factor structure of the questionnaire in a subsample of 308 respondents randomly selected from the sample (SB χ ² (61)=57.4, p =0.61; RMSEA=0.0; 90 percent CI [0.0, 0.031], CFI=1.00). The remaining 708 respondents (393 relatives of cardiovascular unit inpatients and 315 relatives of neuromotor unit inpatients) were used to test measurement invariance between the groups of family members with patients in the two units. The configurial, scalar, and strict factorial invariance provided a good fit to the data. Originality/value: – The QFSR, specifically developed to measure the satisfaction of family members of patients undergoing rehabilitation, appears to be a promising brief questionnaire that can provide important indications for continuous improvement in the delivery of healthcare.